(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study focuses on a comparative analysis of skin treatment methods following laser tattoo removal. The research investigates the morphometric parameters of the skin in white outbred rats after the removal of tattoos, and compares the effectiveness of two treatments: dexpanthenol-containing ointment (Bepanten®) and pomegranate seed oil. The results show that pomegranate seed oil is more effective in promoting skin healing due to its rich composition of acids, vitamins, and antioxidants. This oil provides anti-inflammatory, anti-tumor, and antioxidant benefits, contributing to faster recovery of the skin. The study provides valuable insights into the potential of pomegranate seed oil as an alternative treatment method for post-tattoo removal care.